2015
DOI: 10.13005/msri/120110
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Abaca Fiber Reinforced Urea Formaldehyde Composites

Abstract: The present investigation focuses on the fabrication and mechanical characterization of alkali treated natural abaca fiber reinforced urea formaldehyde composites. The composites were prepared by means of compression moulding, and then the effects of fiber loading on mechanical properties such as tensile strength, flexural strength and impact strength were investigated. The composite with 40 wt% abaca fibers gave excellent tensile strength and flexural strength showing that it has the most superior bonding and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…A somewhat remarkable aspect was the increment of mechanical properties (Fig. 2); the ber loading increased the bending of biomaterial, agreeing with previous studies of Bledzki et al 24 and Suvara et al 13 . However, our results showed that ber loading of 10 and 20% showed the lowest values in MOE f and E f ; this answer is due to the high stickiness of the recycled thermoplastic 2 , and the polarity of the ber could reduce the dispersion of the ber in the matrix (e.g., ber clusters), strongly affecting the resistance of the biomaterial and the generation of free spaces (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A somewhat remarkable aspect was the increment of mechanical properties (Fig. 2); the ber loading increased the bending of biomaterial, agreeing with previous studies of Bledzki et al 24 and Suvara et al 13 . However, our results showed that ber loading of 10 and 20% showed the lowest values in MOE f and E f ; this answer is due to the high stickiness of the recycled thermoplastic 2 , and the polarity of the ber could reduce the dispersion of the ber in the matrix (e.g., ber clusters), strongly affecting the resistance of the biomaterial and the generation of free spaces (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Our composite materials met these standards due to the high mechanical resistance of the M. textilis ber 12 . Generally, The properties of the composite material and its potential for use depend on the physical-mechanical properties of the natural ber 4,22 , ber loading in the matrix 9 , degree of cohesion between ber-thermoplastic 1 , and adaptability of the materials to the extrusion method used 13 .…”
Section: Considerations For Composite Materials Usementioning
confidence: 99%
See 1 more Smart Citation
“…The test results of CG fiber‐epoxy composites reveal that, it is a potential reinforcement material for polymer composites. This is also validated by comparing the test results with the previous research works on thermoset polymer composites made from some natural fibers, like Abaca, [ 32,11 ] Bamboo, [ 33,34 ] Banana, [ 35 ] Coconut sheath, [ 36 ] Coir, [ 37 ] Hemp, [ 38 ] Zea, [ 39 ] Jute, [ 40 ] Kenaf, [41,42] and Pineapple. [43] Most of these selected composites were prepared by same processing conditions, which enables comparison between them.…”
Section: Resultsmentioning
confidence: 64%
“…44 Other treatments reported include the use of benzene diazonium salt, 45 enzymes, 46 and sodium hydroxide 47 with noticeable improvement in mechanical properties as long as properly optimized. Abaca has also been used in conjunction with furan resin, 48 epoxy resin, 49 urea formaldehyde, 50 polylactic acid 51 and high impact polystyrene 52 with moderate success. Plasma treatment of abaca fabric enhanced its adhesion to unsaturated polyester and improved its wettability but exhibited notable low tensile strength even with supplementary mercerization and silylation.…”
Section: Abaca Fibers As Composite Reinforcing Materialsmentioning
confidence: 99%